ANALISIS DAN PERANCANGAN SISTEM INFORMASI LAYANAN KEANGGOTAAN BERBASIS SMS GATEWAY PADA PUSAT KEBUGARAN BODY FIT STATION - Nicodemus Ivan Yorse; Akhmad Budi (Jurnal Informatika dan Bisnis, 2015)
Information and communication technology has recently grown rapidly. It has also penetrated into all areas, from culinary, health, medical, personal interests, and entertainment. It can be seen from the usage of smartphones, tablets, laptops, and other gadgets. Their growth was supported continuously by new innovations from hardware and software developers. The purposes of this research are making the business process of the fitness center become more efficient, and establishing a good relationship with its members. Data was collected from provided documents of the company. The business process was directly observed. Interviews was held with all parties who associated with the business processes at Body Fit Station. Interviews explore recently running business processes and find out the existing problems, as well as how member’s opinions about the business processes at Body Fit Station. The conclusion from this research is, after the implementation of management information system based on SMS gateway make the members can find updated information easily. On the other side, the manager and the owner can view the reports more detail and accurate